Can the cGAS-STING Pathway Play a Role in the Dry Eye? - Ouyang, Weijie; Wang, Shoubi; Hu, Jiaoyue; Liu, Zuguo (Frontiers in Immunology, 2022)
Dry eye is one of the most common ocular surface diseases in the world and seriously affects the quality of life of patients. As an immune-related disease, the mechanism of dry eye has still not been fully elucidated. The cGAS-STING pathway is a recently discovered pathway that plays an important role in autoimmune and inflammatory diseases by recognizing dsDNA. As an important signal to initiate inflammation, the release of dsDNA is associated with dry eye. Herein, we focused on the pathophysiology of the immune-inflammatory response in the pathogenesis of dry eye, attempted to gain insight into the involvement of dsDNA in the dry eye immune response, and investigated the mechanism of the cGAS-STING pathway involved in the immune-inflammatory response. We further proposed that the cGAS-STING pathway may participate in dry eye as a new mechanism linking dry eye and the immune-inflammatory response, thus providing a new direction for the mechanistic exploration of dry eye.